2014
DOI: 10.1063/1.4891312
|View full text |Cite
|
Sign up to set email alerts
|

Clamping-induced changes of domain morphology in 88%Pb(Zn1/3Nb2/3)O3-12%PbTiO3

Abstract: Domain microstructures in single crystal lamellae of 88%Pb(Zn1/3Nb2/3)O3-12%PbTiO3 (cut from bulk using focused ion beam milling) have been mapped using both piezoresponse force microscopy and transmission electron microscopy. Dramatic changes from mottled microstructures typical of relaxors to larger scale domains typical of ferroelectrics have been noted. Stresses associated with substrate clamping are suspected as the cause for the transition from short- to long-range polar order, akin to effects induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The fact that both meso‐ and nanoscale imaging indicated very similar configurations suggests that singularities are both unlikely and unfavorable in complex quadrant domains in ferroelectrics. The same group studied PZN‐12PT lamella placed on their sidewalls on Pt‐coated MgO carriers . They found that the change in clamping between the lamella placed flat and those placed on their sidewalls caused a variation in domain configurations.…”
Section: Domain Engineering and Manipulation Via Fib Nanostructuringmentioning
confidence: 99%
“…The fact that both meso‐ and nanoscale imaging indicated very similar configurations suggests that singularities are both unlikely and unfavorable in complex quadrant domains in ferroelectrics. The same group studied PZN‐12PT lamella placed on their sidewalls on Pt‐coated MgO carriers . They found that the change in clamping between the lamella placed flat and those placed on their sidewalls caused a variation in domain configurations.…”
Section: Domain Engineering and Manipulation Via Fib Nanostructuringmentioning
confidence: 99%